Integration of language research software in university teaching - Ramírez Salado , Mercedes (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The use of specialized software, applications and programs has changed the way we do research, and therefore, the integration of these tools in the university courses is especially important. Thus, this paper presents two computer programs widely used in linguistic research and the methodology followed for their introduction in a specific course. Finally, the results obtained and the students’ degree of acceptance are discussed, leading to the final conclusions.